2015
DOI: 10.3892/or.2015.4360
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 induces breast cancer cell invasion and migration by suppressing smad7 via EGF and TGF-β pathways

Abstract: MicroRNA-21 (miR-21) upregulation, smad family member 7 (smad7) downregulation, epidermal growth factor (EGF) and transforming growth factor-β (TGF-β) actions contribute to breast cancer cell aggressiveness. However, their correlation and the relevant molecular mechanisms involved remain to be elucidated. The present study was undertaken to determine the association of miR-21, smad7, EGF and TGF-β with breast cancer cell invasion and migration and to identify the molecular mechanisms involved using immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 39 publications
0
30
0
2
Order By: Relevance
“…Current evidence suggests that miR-21 may both be a product of and mediator of TGF-β signaling in many pathological conditions [104106]. We identified a 3- to 4-fold increase in miR-21 expression in platinum-sensitive cells treated with platinum-resistant exosomes and in the parental platinum-resistant cells.…”
Section: Discussionmentioning
confidence: 73%
“…Current evidence suggests that miR-21 may both be a product of and mediator of TGF-β signaling in many pathological conditions [104106]. We identified a 3- to 4-fold increase in miR-21 expression in platinum-sensitive cells treated with platinum-resistant exosomes and in the parental platinum-resistant cells.…”
Section: Discussionmentioning
confidence: 73%
“…miR-21 has been reported to function as an onco-miRNA by directly regulating several tumor suppressors, such as tropomyosin 1 (TPM1), programmed cell death 4 (PDCD4), maspin and phosphatase and tensin homolog (PTEN) (21,22). Additionally, it has been reported that miR-21 is involved in certain cancerrelated signaling pathways, such as the PTEN/PI3K/AKT, the ERK1/2/MAPK and the miR-21/smad7/ERK signaling pathways, thus, promoting tumor growth and metastasis in vivo and in vitro (21,(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has indicated that overexpression of miR-21 increased invasion of MCF-7 cancer cells, and enhanced EGF-mediated invasion and TGF-β-mediated invasion in breast cancer [30]. In addition, miR-21 functions as an upstream regulator of IL-10 by targeting the 3' untranslated region of IL-10 mRNA [31].…”
Section: Discussionmentioning
confidence: 98%